Parents’ experiences with a sick or injured child during the COVID-19 lockdown: an online survey in the Netherlands - Henriette A Moll; Monica Lakhanpaul; Ray B Jones; Rachel Carter; Dorine M Borensztajn; Jade Chynoweth; Sarah Neill; Chantal D Tan; Eveline K Lutgert (BMJ Open)
Objective To assess the impact of the COVID-19 lockdown on parents’ health-seeking behaviour and care for a sick or injured child in the Netherlands.Design and setting An online survey on parents’ experiences with a sick or injured child during the COVID-19 lockdown periods was disseminated through social media.Participants Parents living in the Netherlands with a sick or injured child during the lockdown periods from March to June 2020 and from December 2020 to February 2021 were eligible to participate.Outcome measures Descriptive statistics and thematic analysis were used to analyse family and children’s characteristics, parents’ response to a sick or injured child, and the perceived impact of the lockdown on child’s severity of illness and treatment reported by parents. Analyses were stratified for children with and without chronic conditions.Results Of the 105 parents who completed the survey, 83% reported they would have sought medical help before lockdown compared with 88% who did seek help during lockdown for the same specific medical problem. Parents reported that changes in health services affected their child’s severity of illness (31%) and their treatment (39%), especially for children with chronic conditions. These changes included less availability of healthcare services and long waiting lists, which mostly led to worsening of the child’s illness. During lockdown, there was no change in health-seeking behaviour by parents of children with a chronic condition (N=51) compared with parents of children without a chronic condition.Conclusion Parents in the Netherlands who completed the survey were not deterred from seeking medical help for their sick or injured child during the COVID-19 lockdown periods. However, changes in health services affected child’s severity of illness and treatment, especially for children with chronic conditions.